Intellectual Property Rights in Biotechnology and Health Care — Results of a Stakeholder Dialogue - World Business Council for Sustainable Development (WBCSD); Wissenschaftszentrum Berlin für Sozialforschung - Social Science Research Center Berlin (WZB) (WBCSD, 2003)
This report presents the results from a stakeholder dialogue launched by the WBCSD, which involved some 40 participants from major companies, non-governmental organizations, and legal and political experts in extended discussions over controversial issues of intellectual property rights in the application of modern biotechnology to medical R&D. The dialogue process was moderated by the Social Science Research Center Berlin (WZB). It took place from May 2001 to July 2002 and proceeded through face-to-face meetings and via internet exchanges, engaging participants in three topics: access to human genetic resources, protection of traditional knowledge, access to essential medicines. While the participants retained their diverging perspectives and concerns in many respects, they were nevertheless able to identify some common ground regarding the nature of the problems and possible options for dealing with them. The main emphasis was on what companies could do, and should do, within their corporate strategies to address these controversial issues.
Keywords: 300; biotechnology; medicine; health care delivery system; legal position; copyright; patent law; genetics; international law; research results; entrance requirements; developing country; economic factors; international relations